(927) Problems of Long-term Planning in the German Democratic Republic مشاكل التخطيط الطويل الاجل في جمهورية ألمانيا الديمقراطية - Manfred Engert (INP, 2024)
Economy of the German Democratic Republic (G.D.R.) is undergoing basic changes in its central planning system, with an increasing focus on long-term policies and planning. The growing emphasis on long-term planning is driven by several main reasons: First, the scale of economic, technological, and social problems is rapidly increasing, Second, the resources and funds required to solve these problems have become immense, often exceeding the economic capacity of large companies or even entire industries. Third, the comprehensive and complex nature of these problems necessitates large-scale solutions, primarily at the national level.